A statistical study of space hurricanes in the Northern Hemisphere - Lu, Sheng; Xing, Zan-Yang; Zhang, Qing-He; Zhang, Yong-Liang; Ma, Yu-Zhang; Wang, Xiang-Yu; Oksavik, Kjellmar; Lyons, L. R.; Nanan, Balan; Liu, Jing; Wang, Yong; Deng, Zhong-Xin; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The space hurricane is a newly discovered large-scale three-dimensional magnetic vortex structure that spans the polar ionosphere and magnetosphere. At the height of the ionosphere, it has strong circular horizontal plasma flow with a nearly zero-flow center, and a coincident cyclone-shaped aurora caused by strong electron precipitation associated with intense upward magnetic field-aligned currents. By analyzing the long‐term optical observation onboard the Defense Meteorological Satellite Program (DMSP) F16 satellite from 2005 to 2016, we found that the space hurricane in the Northern Hemisphere occurs in summer and has a maximum occurrence rate in the afternoon sector around solar maximum. In particular, the space hurricanes are more likely to occur in the dayside polar cap at magnetic latitude greater than 80°, and their MLT (magnetic local time) dependence shows a positive relationship with the IMF (interplanetary magnetic field) clock angle. We also found the space hurricane occurs mainly under dominant positive IMF By and Bz and negative Bx conditions. It is suggested that the stable high-latitude lobe reconnection, which occurs under the conditions of large Earth’s dipole tilt angle and high ionosphere conductivity in summer, should be the formation mechanism of space hurricanes. The result will give a better understanding of the solar wind-magnetosphere-ionosphere coupling process under northward IMF conditions.